Pegada hídrica no sistema produtivo numa olaria de cerâmica vermelha no Ceará - Arlindo, Vinícius José Correia (Universidade Federal Rural do Semi-Árido, 2019)
The industrial segment is largely responsible for significant impacts on the environment, either by the consumption of natural resources, that is, by the use of the environment as a means of diluting the pollution generated. The ceramic sector, where the non-metallic mineral processing industry is located, not unlike the other segments, also has relevant impacts on the environment. The production of ceramic blocks, an industry of great presence in northeastern Brazil, presents productive aspects directly related to soil, air and water. Therefore, it is important that such aspects should be studied in order to understand their impacts and damages. The present work has as objective to realize the water footprint in the productive system of a pottery of red ceramics in the state of Ceará. Using the water footprint as a tool to analyze the use of a resource, in order to observe a lower value than expected when compared to similar studies. This fact will be discussed mainly by relating the climatic interference that directly affects one of the main inputs, the clay.
Keywords: Indústria cerâmica; impactos ambientais; racionalização de recursos.; Ceramics industry; environmental impacts; rationalization of resources; ENGENHARIAS::ENGENHARIA SANITARIA